IMPROVING THE METHODOLOGY OF SQUALENE EXTRACTION FROM PALM FATTY ACID DISTILLATE (PFAD) THROUGH ENHANCED PRE-TREATMENT PROCESS - Widiputri, Diah Indriani; Jayaratana, Adianto; Legowo, Evita Herawati (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2020)
Palm Fatty Acid Distillate (PFAD) resulted from refinery process of crude palm oil (CPO) contains some beneficial bioactive compounds such as squalene, which is one of the best natural emollients for pharmaceuticals and cosmetics. The need to overcome the problem with the abundant amount of PFAD as a waste has led to the attempts to extract squalene from PFAD in single and multiple stage processes. However, many impurities such as free fatty acids were still found to be present in the yielded squalene extract. Therefore, in this research an effort to optimize the pre-treatment process prior to the extraction was conducted by applying separation technique to reduce some of the free fatty acid, which did not react during saponification. From this experiment, three different pre-treatment scenarios in single stage extraction showed that the squalene content rose from 5.37 % to 9.32 % when centrifugation was applied. Adding another round of saponification to this method has increased the content even further to 23.94 %. Furthermore, the application of multiple stage extraction could increase the squalene content to 37.45 %. Keywords: Palm Fatty Acid Distillate (PFAD), Squalene, Liquid-liquid Extraction, Multiple stage extraction, Centrifugation process